Indoor environmental control of tuberculosis and other airborne infections. (7th October 2015) - Nardell, E. A.
Abstract: Tuberculosis (TB) remains the airborne infection of global importance, although many environmental interventions to control TB apply to influenza and other infections with airborne potential. This review focuses on the global problem and the current state of available environmental interventions. TB transmission is facilitated in overcrowded, poorly ventilated congregate settings, such as hospitals, clinics, prisons, jails, and refugee camps. The best means of TB transmission control is source control— to identify unsuspected infectious cases and to promptly begin effective therapy. However, even with active case finding and rapid diagnostics, not every unsuspected case will be identified, and environmental control measures remain the next intervention of choice. Natural ventilation is the main means of air disinfection and has the advantage of wide availability, low cost, and high efficacy—under optimal conditions. It is usually not applicable all year in colder climates and may not be effective when windows are closed on cold nights in warm climates, for security, and for pest control. In warm climates, windows may be closed when air conditioning is installed for thermal comfort. Although mechanical ventilation, if properly installed and maintained, can provide adequate air disinfection, it is expensive to install, maintain, and operate. The most cost‐effective way to achieve high levels of air disinfection is upper room germicidal irradiation. The safe and effective application of this poorly defined intervention is now well understood, and recently published evidence‐based application guidelines will make implementation easier.